Adolescent Sleep Insufficiency One Year After High School - Perlus, Jessamyn G. (J Adolesc, 2018)
INTRODUCTION: Sleep difficulties affect approximately 45% of adolescents and are associated with health consequences such as depression and obesity. Sleep duration immediately following high school is not well understood, especially for those not pursuing post-secondary education. We examined adolescent sleep insufficiency and its association with school and work status. METHODS: Data were collected in 2012 and 2013 as part of the NEXT Generation Health Study (NEXT), a nationally representative, longitudinal study of U.S. adolescents. Self-reported sleep was compared with guidelines for healthy sleep. RESULTS: On weekdays, 31% reported less than 7 hours of sleep; which reduced to 6% on weekends. Average weekday sleep was 7.4 hours and weekend sleep was 9.2 hours. Few results emerged from interaction analyses comparing different work and school statuses. CONCLUSIONS: This study captures sleep habits of adolescents one year after high school regardless of school and/or working status. Implications and future directions are discussed.